SYNTHESIS, LABELING, AND BIODISTRIBUTION TEST OF MESO -5, 15 -DI [3, 4 -BIS (CARBOXY METHYLEN OXY) PHENYL] PORPHYRIN AND MESO -5, 15 -DI [3, 4 -BIS (CARBOXY METHYLEN OXY) PHENYL], 10, 20 -DIPHENYL PORPHYRIN AS THERANOSTIC RADIOPHARMACEUTICAL LIGAND - Zein Mutaqin, Faujan (D/g, and remained at 0.81 %ID/g level at 24 hours post-injection. The 186 Re- D3,4BCPDPP tumour/blood ratio at 2, 4, and 24 hours post-injection were 0.6; 0.9; and 1.1 respectively. While the 186 Re-D3,4BCPDPP tumour/muscle ratio at 2, 4, and 24 hours post-injection were 3.5; 3.4; dan 6.2 respectively. It indicates the selectivity of 186 Re-D3,4BCPDPP to the cancer cells. Based on the results, it can be concluded that 186 Re-D3,4BCPDPP is potential to be developed as a safe and effective radiopharmaceutical for the cancer diagnosis and therapy.)
Cancer is one of diseases that causes the highest mortality in the world. Late detection of cancer will increase the risk of mortality to the patients. Actually, low level stadium cancer can be overcome with several kinds of cancer therapy. Thus, early detection and therapy will lower the risk of mortality to the patiens. All this time, the cancer treatment is carried out using radiation, chemotherapy, combination of radiation and chemotherapy, and surgery. Cancer treatment using radiation is still unable to give satisfactory results, whereas chemotherapy is not selective and often induces a second primary cancer as a result of the carcinogenic properties generally owned by the compounds. Similarly, removal of the cancer tissue by surgery is still incomplete. Therefore, it is necessary to find more effective and safe techniques for cancer diagnosis and therapy. Cancer diagnosis and therapy using radiopharmaceuticals is one of the best alternatives to overcome this problem. By labeling gamma and beta emitting radionuclides to a carrier compounds which selectively bind to the cancer tissue will produce a safe and potential radiopharmaceutical. The gamma radiation of radionuclide can be used for diagnosis, while the amount of energy from the beta particles can be used to kill cancer cells. The role of the carrier compound to deliver the gamma and beta radiation to the cancer cells will lead the appropriate selective and safe diagnosis and treatment. Porphyrin and its derivatives are widely investigated for cancer therapy because of their high selectivity to cancer cells. This study aimes to synthesize novel water soluble porphyrins, meso -5, 15 -di [3, 4 -bis (carboxy methylen oxy) phenyl] porphyrin (D3,4BCPP) and meso -5, 15 -di [3, 4 -bis (carboxy methylen oxy) phenyl], 10, 20 -diphenyl porphyrin (D3,4BCPDPP), to label the porphyrins by the gamma or beta emitting radionuclides, and to perform biodistribution test of labeled-porhyrin as radiopharmaceutical candidate for cancer diagnosis or therapy. In this research, the study was carried out firstly by molecular modeling and toxicity prediction to predict the stability and safety of the porphyrins and the possibility to label them by radionuclides. The results of molecular modeling v calculations using density functional theory methods showed that the D3,4BCPP and D3,4BCPDPP compounds had a low total energy which indicate that both compounds are stable. The carboxylic groups on the meso substituent of the D3,4BCPP and D3,4BCPDPP compounds can be labeled by Rhenium radionuclides to produce the more stable Re-D3,4BCPP and Re-D3,4BCPDPP complexes even though they have molecular changes based on the length and angle of the chemical bond, the total energy of the molecule and the electron distribution. Toxicity prediction using ADMET Predictor™ showed that D3,4BCP has an acute toxicity in rat; D3,4BCPDPP has an acute toxicity in rat and hepatotoxic; Re-D3,4BCPP has an acute toxicity in rat, hepatotoxic, and likely carcinogenic in rat in which requiring microsomal activation mechanism; and Re- D3,4BCPDPP has an acute toxicity in rat and hepatotoxic. However, the all toxicities can occur if the concentration is higher than the toxic dose (above 3.16 mg/kg body weight/day). The synthesis of D3,4BCPP and D3,4BCPDPP was carried out using modified Lindsey and Wagner methods using dipyrromethane and 5-phenyldipyrromethane, resulting a pure water soluble purple crystaline. Both compounds were characterized by NMR spectroscopy. Labeling of D3,4BCPDPP and D3,4BCPP by 186 Re radionuclide gave 186 Re- D3,4BCPDPP and 186 Re-D3,4BCPP complexes with 92% and 91.6% labeling effectivity respectively, wich was obtained by transchelating reaction procedure with optimal condition at pH 4 – 5, SnCl2 as reductor, 60 minutes incubation at room temperature, and the addition of vitamin C to improve complex stability. The biodistribution test in normal and cancer-induced mice showed a low retention of 186 Re-D3,4BCPDPP in several vital organs. In cancer-induced mice, the 186 Re-D3,4BCPDPP uptake in tumour at 2 hours post-injection was 1.45